Relationship between plasma hormones and anthropometric measures of muscle mass in postmenopausal women - Orsatti, Fábio Lera; De Oliveira, Erick Prado [UNESP]; Burini, Roberto Carlos [UNESP] (Springer Nature, 2012)
The muscle undoubtedly pertains to a complex mechano-biological system that primarily enables efficient locomotion but is also involved in other vital physiological functions. Aging is accompanied by progressive reduction in muscle mass (sarcopenia). Sarcopenia is a progressive process that occurs in healthy individuals. Sarcopenia is usually associated with functional impairment and physical disability, especially in women, and is the direct cause of reduction in muscle strength. Muscle mass and strength start declining over the perimenopausal years and this phenomenon seems to be partly estrogen-dependent. The role of estrogen in sarcopenia remains unclear. Epidemiological studies suggest that as estrogen declines with age there is an increase in the levels of pro-inflammatory cytokines suspected to be involved in the sarcopenia process such as tumor necrosis factor alpha and interleukin-6 (IL-6). These cytokines cause an imbalance in muscle tissue synthesis in favor of excess protein breakdown. Epidemiological studies suggest a relationship between low levels of testosterone and loss of muscle mass, strength and function. In post-menopausal women testosterone increases muscle mass. Despite evidence that DHEA supplementation results in an increase of blood testosterone levels in women and increase of IGF-1 in men, few studies have reported an effect in muscle size, strength or function. Insulin-like growth factor-1 (IGF-1) and growth hormone (GH) decline with age. GH replacement therapy lowers fat mass and increases lean body mass. The aging muscle is capable of synthesizing IGF-1 but it may be less sensitive to IGF-1 and could have an attenuated ability to synthesize an isoform of IGF-1 promoting satellite cell proliferation. Exercise may reverse the resistance of aging muscle to IGF-1.